An electric concentrator and thermal cloaking device. (13th May 2020) - Raza, Muhammad
Abstract: The concentration and cloaking phenomena of physical fields in Metamaterials has captured the attention of the researchers due to their simplified approaches. However most of the work conducted is focussed on controlling single physical field. Transformation optics has paved the way for developing intelligent bifunctional devices. Bifunctional devices are such controlled devices which execute two different physical functions simultaneously and independently. In this work we have applied the transformation optics theory to design a multilayered two dimensional spherical bifunctional device which behaves like an electric concentrator and thermal invisibility cloak simultaneously. Moreover, we have also observed the normalized behavior of the proposed device. The simulation performance confirms the feasibility of our suggested model.